Strategi Merdeka Belajar Menulis Cerita Pendek Karakter Bangsa Untuk Meningkatkan Keterampilan Berpikir Kreatif Mahasiswa Melalui Pendidikan Kewarganegaraan - Zaenul Slam (Allimna: Jurnal Pendidikan Profesi Guru, 2023)
This study aims to describe how to improve students' creative thinking skills in Civic Education  (CE) through the Freedom to Learn  strategy  to write National Character Short Stories (NCSS). This research is a Research and Development (R&D) development study using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The results showed that NCSS had been developed using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. The results showed that the quality of NCSS was: (a) the completeness of the formal aspect averaged 87.59 (Very Good); completeness of intrinsic elements average acquisition of 87.59 (Very Good); (c) integration of structural elements with an average score of 81.10 (Good), and (d) language suitability with an average score of 83.53 (Good). The overall gain is an average of 84.95 (Good). In conclusion, the Freedom to Learn to write NCSS strategy in Civic Education has a direct impact (instructional effect) on improving students' creative thinking skills. NCSS products developed using the ADDIE model are suitable for use as a reading supplement for the Strengthening Character Education Movement for students and the community.